Gamma-Glutamyl Transpeptidase-to-Platelet Ratio Predicts Significant Liver Fibrosis of Chronic Hepatitis B Patients in China - Tianyi Ren; Huan Wang; Ruihong Wu; Junqi Niu (Gastroenterology Research and Practice)
Background and Aims. We want to investigate whether a novel noninvasive marker is suitable for Chinese CHB patients. Methods. A total of 160 treatment-naïve CHB patients who underwent liver biopsy were enrolled in our study, and we assessed the diagnostic accuracies of GPR, aspartate transaminase-to-platelet ratio index (APRI), and the fibrosis index based on 4 factors (FIB-4) in them. Results. Of these 160 CHB patients, the numbers of F0, F1, F2, F3, and F4 are 34 (21.3%), 62 (38.8%), 18 (11.3%), 24 (15%), and 22 (13.8%), respectively. The area under the receiver operating characteristic curves (AUROC) of GPR for fibrosis (0.77 versus 0.70, P=0.03), significant fibrosis (0.70 versus 0.63, P=0.02), and extensive fibrosis (0.71 versus 0.64, P=0.02) were significantly higher than those of APRI. The AUROCs of GPR and Fib-4 for fibrosis (0.77 versus 0.75, P=0.14), significant fibrosis (0.70 versus 0.70, P=0.22), extensive fibrosis (0.71 versus 0.68, P=0.13), and cirrhosis (0.64 versus 0.67, P=0.24) were comparable. Conclusions. The GPR can be a routine laboratory marker to stage liver fibrosis in patients with CHB in China.